MARKETING OF LOCAL BRANDS: HOW CONSUMER LOYALTY IS FORMED THROUGH THE SUPPORT OF LOCAL PRODUCTION - Graf-Gudz, Svetlana (SWorldJournal, 2025)
The article explores the mechanisms behind the development of consumer loyalty toward local brands through support for local production and the specifics of marketing strategies tailored to local markets. The aim of the article is to identify the key mech